2007
DOI: 10.1080/10640260701454394
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spirituality in the Treatment of Trauma and Eating Disorders: Recommendations for Clinical Practice

Abstract: The relationships among trauma, eating disorders, and spirituality are complex. Both trauma and eating disorders can distance women from their own spirituality, which undermines a potentially important treatment resource. In this article, we offer suggestions based on our clinical experience for helping eating disorder patients who have suffered trauma to rediscover their faith and spirituality. We describe how spirituality can be used as a resource to assist women throughout treatment and in recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 13 publications
2
24
0
2
Order By: Relevance
“…In a qualitative survey of 24 inpatients with eating disorder who had experienced various forms of trauma (i.e., sexual abuse, physical abuse, emotional abuse, serious illness, divorce of parents, death of family members), Berrett, Hardman, O'Grady, and Richards (2007) found that patients perceived that the trauma they had experienced had injured their sense of spirituality. Many of the patients also perceived that recovering their faith and sense of spirituality was an important part of their journey toward recovery.…”
Section: Empirical Connections Between Trauma and Spiritualitymentioning
confidence: 99%
“…In a qualitative survey of 24 inpatients with eating disorder who had experienced various forms of trauma (i.e., sexual abuse, physical abuse, emotional abuse, serious illness, divorce of parents, death of family members), Berrett, Hardman, O'Grady, and Richards (2007) found that patients perceived that the trauma they had experienced had injured their sense of spirituality. Many of the patients also perceived that recovering their faith and sense of spirituality was an important part of their journey toward recovery.…”
Section: Empirical Connections Between Trauma and Spiritualitymentioning
confidence: 99%
“…Although clients may report engaging primarily in one type of religious coping, clients may also voice an inner conflict about religious beliefs. Berrett, Hardman, O'Grady, and Richards (2007) described a client who seemed to experience such an internal conflict; this client, who struggled with an eating disorder, noted that she presently lacked trust in God, but cognitively realized a need to “rebuild that trust” (p. 376). Researchers also reported that some clients with eating disorders changed certain religious beliefs during the course of therapy (Marsden, Karagianni, & Morgan, 2007).…”
Section: Implications For Counseling Practicementioning
confidence: 99%
“…Para algunos autores, tanto las experiencias traumáticas como los TCA pueden distanciar a las mujeres de su propia espiritualidad, socavando una fuente terapéutica potencialmente importante 59,60 . Las intervenciones espirituales son escasamente utilizadas en los programas de tratamientos contemporáneos y existe poca confi rmación en la práctica clínica disponible en relación a su efi cacia; no obstante, se dispone de publicaciones concluyentes que se refi eren al valor del componente espiritual en las aproximaciones terapéuticas a considerar en estas pacientes.…”
Section: Abordajes Terapéuticos Religiosos Y Espiritualesunclassified